APOBEC3A drives deaminase mutagenesis in human gastric epithelium - An, Yohan; Lee, Ji-Hyun; Lim, Joonoh; Youk, Jeonghwan; Park, Seongyeol; Park, Ji-Hyung; Yi, Kijong; Kim, Taewoo; Nam, Chang Hyun; Lee, Won Hee; Oh, Soo A; Bae, Yoo Jin; et al. (Genome Research, 2025)
Cancer genomes frequently carry apolipoprotein B mRNA editing catalytic polypeptide-like (APOBEC)-associated DNA mutations, suggesting APOBEC enzymes as innate mutagens during cancer initiation and evolution. However, the pure mutagenic impacts of the specific enzymes among this family remain unclear in human normal cell lineages. Here, we investigate the comparative mutagenic activities of APOBEC3A and APOBEC3B, through whole-genome sequencing of human normal gastric organoid lines carrying doxycycline-inducible APOBEC expression cassettes. Our findings demonstrate that transcriptional upregulation of APOBEC3A leads to the acquisition of a massive number of genomic mutations in just a few cell cycles. In contrast, despite clear deaminase activity and DNA damage, APOBEC3B upregulation does not generate a significant increase in mutations in the gastric epithelium. APOBEC3B-associated mutagenesis remains minimal even in the context of TP53 inactivation. Further analysis of the mutational landscape following APOBEC3A upregulation reveals a detailed spectrum of APOBEC3A-associated mutations, including indels, primarily 1 bp deletions, clustered mutations, and evidence of selective pressures acting on cells carrying the mutations. Our observations provide a clear foundation for understanding the mutational impact of APOBEC enzymes in human cells.